THE RELATIONSHIP BETWEEN BUREAUCRACY AND DEVELOPMENTS IN MANAGEMENT ACCOUNTING, 1700-2023: AN OVERVIEW - Costa Oliveira, Helena; Craig, Russell; Rodrigues, Lúcia Lima (UI Scholars Hub, 2023)
Bureaucracy has co-existed with forms of management accounting [MA] from the time of ancient civilizations. In this paper, we review literature in a wide variety of scholarly journals and books to provide an overview of this co-existence. We trace the historical evolution of MA and how it was influenced by bureaucracy from 1700 to the present. We do so through four time periods, designated classical, modern, post-modern and contemporary. For each of these periods, evolving understandings of bureaucracy were linked to changes in the practice and conceptualization of MA. In the classical period (1700 – 1950), developments in MA corresponded to a prevailing positive understanding of bureaucracy. In the modern period (1951 – 1980), theoretical elaborations of MA assimilated a post-bureaucratic posture. In the post-modern period (1981 – 1990), changes in MA practice partially mirrored ongoing criticism of bureaucracy. In the contemporary period (1991 – present), MA practices have reflected a more favorable disposition to the idea of bureaucracy.